Targeting Gli Transcription Activation by Small Molecule Suppresses Tumor Growth - Bosco-Clément, Geneviève (2013)
Targeted inhibition of Hedgehog signaling at the cell membrane has been associated with anti-cancer activity in preclinical and early clinical studies. Hedgehog signaling involves activation of Gli transcription factors that can also be induced by alternative pathways. In this study we identified an interaction between Gli proteins and a transcription co-activator TAF9, and validated its functional relevance in regulating Gli transactivation. We also describe a novel, synthetic small molecule, FN1-8, that efficiently interferes with Gli/TAF9 interaction and down-regulate Gli/TAF9 dependent transcriptional activity. More importantly, FN1-8 suppresses cancer cell proliferation in vitro and inhibits tumor growth in vivo. Our results suggest that blocking Gli transactivation, a key control point of multiple oncogenic pathways, may be an effective anti-cancer strategy.